Synthesis and Antibacterial Activity of some Carbamoylphenoxy Derivatives of S-Triazine - Desai, Pratibha; Champaneri, A.C.; Desai, K.R. (Asian Journal of Chemistry, 2010)
2-(2´-Carbamoyl-phenoxy)-4-(3´-methyl anilino )-6-aryl-ureido compound has been condensed with S-triazine and substituted with nitro, methyl, methoxy and chloro groups at various positions in aryl ureido group and their antibacterial activity has been screened.